Decoding the Therapeutic Potential of [HuArgI (Co)-PEG5000] Arginase Treatment - Zeineddine, Mira (2023)
Targeting specific biological processes through innovative therapeutic techniques is necessary to enhance patient outcomes, as breast cancer is still a major global health concern. With a particular emphasis on the impact of arginase-induced autophagy, we examined the complex interactions among autophagy, Rho GTPases, and cell migration in breast cancer cells in this work. Our results identify a unique regulatory axis whereby arginine deprivation induces strong autophagic responses in breast cancer cells, which, because of disturbed autophagy flux, accumulate autophagosomes. Additionally, during arginine starvation, we noticed a remarkable downregulation of RhoA activation, which corresponded with inhibited cell motility. Chloroquine-induced autophagy suppression was notably ineffective in restoring cell migration, underscoring the importance of Rho GTPase signaling pathways, particularly RhoA, in controlling the motility of breast cancer cells. Furthermore, independent of autophagy, our research revealed that the PI3K/mTOR pathways are important regulators of cell migration. The significance of PI3K in breast cancer cell motility was highlighted by the efficient prevention of cell migration achieved by the pharmacological intervention of wortmannin, a powerful PI3K inhibitor. Notably, our study shows that deciphering the context-dependent functions of signaling pathways is essential to understanding the intricacies of cancer cell behavior. Through the process of unraveling the complex relationships among autophagy, Rho GTPases, and cell migration, we have been able to highlight points of vulnerability in cancer cells. By focusing on these pathways, it may be possible to develop highly specialized therapies and customized treatment regimens, which would completely alter the way that breast cancer is treated. Moreover, our study results lay the groundwork for the creation of innovative combination treatments that specifically target different facets of cancer cell behavior, offering patients with breast cancer better prognoses and increased therapeutic efficacy.